Morphological effects of flooding on Styrax pohlii and the dynamics of physiological responses during flooding and post-flooding conditions - Kissmann, Camila [UNESP]; Veiga, Eduardo Borges da [UNESP]; Eichemberg, Mayra Teruya; Habermann, Gustavo [UNESP] (Elsevier B.V., 2014)
Styrax pohlii naturally occurs in flood-prone areas and its capacity to survive floods is intriguing. Here we checked whether flooded potted plants of this species develop adventitious roots with aerenchyma, how rapid phenoplastic reactions are and whether these reactions are reflected in photosynthetic performances and growth. Potted plants were flooded (water level at 3 cm above the soil surface) for 100 days, and subsequently recovered under soil field capacity conditions for 50 days. Another group of plants were maintained under control (nonflooded) conditions for 150 days. Biomass of organs, growth parameters, leaf gas exchange, and chlorophyll fluorescence were measured in flooded and control plants. Adventitious roots started emerging 15 days after flooding (DAF), but no aerenchyma was observed. Flooding conditions reduced growth and biomass, which was strongly related to reductions in CO2 assimilation rates (A) and stomatal conductance (gs) 25 DAF. Photochemical performances were not as affected by flooding conditions as gas exchange variables, which took 17-20 days to recover. Photosynthesis was not biochemically affected, as A/Ci curve components remained unchanged. S. pohlii plants rely on adventitious roots with narrow intercellular spaces to survive flooding conditions, and this species is physiologically capable of fast recovery from flooding periods. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomass; Leaf gas exchange; Photochemical performance; Styracaceae; Waterlogged environment